Identification of neural circuits controlling male sexual behavior and sexual motivation by manganese-enhanced magnetic resonance imaging - Gaytán-Tocavén, Lorena; Aguilar-Moreno, Alejandro; Ortiz, Juan; Alcauter, Sarael; Antonio-Cabrera, Edwards; Paredes, Raúl G. (Frontiers in Behavioral Neuroscience, 2023)
Different techniques have identified the brain regions controlling sexual motivation and sexual behavior. However, the influence of sexual experience on the activation of these brain regions in the same subject is unknown. Using manganese-enhanced magnetic resonance imaging (MEMRI), we analyzed the activation of brain regions in the sexual incentive motivation (SIM) and the partner preference PP (tests), on weeks 1, 5 and 10, in male rats tested for ten weeks. AIMS. In experiment 1, we analyzed the possible toxic effects of 16 mg/kg of MnCl2 on male sexual behavior, wheel running, and motor execution. In experiment 2, subjects were tested for SIM and PP using MEMRI.METHODS. In both experiments, a dose of 16mg/kg (s.c) of chloride manganese (MnCl2) was administered 24 h before subjects were tested and placed immediately thereafter in a 7 tesla Brucker scanner. RESULTS. In experiment 1, the dose of 16mg/kg of MnCl2 did not induce behavioral alterations that could interfere with interpreting the imaging data.In experiment 2, we found a clear preference for the female in both the SIM and PP tests.We found a higher signal intensity in the olfactory bulb (OB) in week 1 in the SIM test compared to the control group. We also found increased signal intensity in the sociosexual behavior and mesolimbic reward circuits in the SIM test in week 1. In the PP test, we found a higher signal intensity in the ventral tegmental area (VTA) in week 10 compared to the control group. In the same test, we found increased signal intensity in the socio-sexual and mesolimbic reward circuits in week 5 compared to the control group. The Cohen's D analysis for the whole brain in the group repeatedly tested in the SIM group revealed that as the subjects gained sexual experience, we observed higher brain activation in the OB. The PP group showed higher brain activation in the cortex and subcortical structures as they acquired sexual experience. CONCLUSION. As the subjects gain sexual experience, more structures of the reward and socio-sexual circuits are recruited, resulting in different and large brain activation.